2020
DOI: 10.1002/vzj2.20043
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of preferential flow to tile drainage varies spatially and temporally

Abstract: Tile drainage of agricultural fields is a conduit for nutrient losses. Preferential flow in the soil can more directly connect surface runoff with tile drainage compared with matrix flow, which may also increase P losses. In this study, water temperature was monitored in surface runoff and tile drainage and electrical conductivity (EC) was measured in tile drainage at two sites in southern Ontario with different soil types (i.e., clay and loam). These data were used to estimate the percentage of preferential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 72 publications
(127 reference statements)
1
24
0
Order By: Relevance
“…More cumulative preferential flow generally corresponded to greater f PF values detected in the first 24 h of drainage of high drainage rates (Figure S4), yet preferential flow often persisted through the inter‐event drainage period. This result suggests that the preferential flow detected throughout each event had an inherent travel time distribution that was selective to rapid transport (e.g., more event water appearing in drainage in first 24 h) but nonetheless incorporated a relevant proportion of water that required multiple days to drain (Pluer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…More cumulative preferential flow generally corresponded to greater f PF values detected in the first 24 h of drainage of high drainage rates (Figure S4), yet preferential flow often persisted through the inter‐event drainage period. This result suggests that the preferential flow detected throughout each event had an inherent travel time distribution that was selective to rapid transport (e.g., more event water appearing in drainage in first 24 h) but nonetheless incorporated a relevant proportion of water that required multiple days to drain (Pluer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The increased P losses in tile drainage that have been observed in the southwestern management region have not been observed in the loamier, undulating soils in the northeastern management region (Lam et al., 2016b). Although there is preferential flow in loam soils in this region (Pluer et al., 2020), there is a greater degree of interaction between macropores and soils (Grant, Macrae, & Ali, 2019) and more buffering of P by subsoils (Plach, Macrae, Ali, et al., 2018); consequently, the contribution of tile drains to edge‐of‐field P losses is small relative to their hydrologic contribution (Plach et al., 2019; Van Esbroeck et al., 2016). The fact that tiles are spaced more widely and are installed deeper in loams than in clay may also be a factor.…”
Section: Regional Conservation Practice Strategiesmentioning
confidence: 98%
“…This primarily occurs on saturated soils (Macrae et al., 2019) rather than as infiltration‐excess runoff over frozen soils, which is more common in regions with more severe winters (Dumanski et al., 2015; Gray et al., 2001). Although tiles flow at their maximum capacity during these events (Macrae et al., 2007b), P losses through tiles are often less than those in the surface runoff that occurs simultaneously (Van Esbroeck et al., 2016; Plach et al., 2019) due to strong buffering potential in the subsurface (Plach, Macrae, Williams, et al., 2018; Plach, Macrae, Ali, et al., 2018) and less preferential connectivity than clay soils (e.g., Grant, Macrae, Rezanezhad, et al., 2019; Macrae et al., 2019; Pluer et al., 2020). Moreover, most runoff occurs before spring fertilizers have been applied.…”
Section: Regional Differences Reveal Challenges For One Size Fits All P Managementmentioning
confidence: 99%
“…Previous studies have either used total Q, preferential flow, or new/old water estimates to predict P concentrations and loading in tiles. For instance, Pluer et al (2020) found that preferential flow (estimated by conductivity based unmixing) was weakly correlated with P concentration, although the relationship between P and preferential flow was positive suggesting that preferential flow was a significant driver of P transport to tiles (Grant et al, 2019;Pluer et al, 2020). Given the relatively low cost of specific conductance, flow, and temperature sensors, widespread application of pathway-connectivity frameworks across environmental and management gradients has significant potential for advancing our understanding of contaminant transport in tiledrainage.…”
Section: Implications For P Delivery At the Edge Of Fieldmentioning
confidence: 99%